2008
DOI: 10.1016/s1472-6483(10)60298-2
|View full text |Cite
|
Sign up to set email alerts
|

Implantation, clinical pregnancy and miscarriage rates after introduction of ultrasound-guided embryo transfer

Abstract: The purpose of this study was to compare the reproductive outcome of ultrasound-guided (USG) embryo transfers versus clinical touch embryo transfers. A statistically powered retrospective analysis of women undergoing fresh and frozen embryo transfers in a National Health Service-based tertiary referral centre in the Department of Reproductive Medicine, St Mary's Hospital, Manchester was carried out. A total of 1723 embryo transfers were included in the analysis. The implantation rate was significantly higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Use of US guidance during embryo transfer has been widely accepted as an important procedure in IVF. This study confirmed previous findings that US-guided embryo transfer is associated with higher pregnancy rates [ 4 , 5 , 6 , 8 ], but how it actually improves the pregnancy outcome is not known. Avoidance of endometrial induction may be one of the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Use of US guidance during embryo transfer has been widely accepted as an important procedure in IVF. This study confirmed previous findings that US-guided embryo transfer is associated with higher pregnancy rates [ 4 , 5 , 6 , 8 ], but how it actually improves the pregnancy outcome is not known. Avoidance of endometrial induction may be one of the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 90%
“…The IUI technique has been shown to be important; recent publications show that atraumatic and ultrasound (US)-guided embryo transfer improves the pregnancy outcomes of IVF cycles [ 4 , 5 ]. Using US guidance during embryo transfer in IVF increases the frequency of ‘easy’ transfer and prevents the catheter from touching the uterine fundus, which may cause uterine contractions [ 6 ]. Similarly, using US guidance during IUI may improve results, but few studies have investigated the effect of US-guided IUI on pregnancy outcomes [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound was introduced with the hope that it would diminish the likelihood that the embryo transfer catheter would traumatize the endometrium as compared with a blind approach or touch technique. With regard to the transfer of fresh embryos in eight RCTs and four cohort studies, transabdominal (TA) ultrasound-guided embryo transfer was found to improve the implantation rate and/or pregnancy rate (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), clinical or ongoing clinical pregnancy rates, and/or livebirth rate (33,36,(41)(42)(43). These findings were supported by five meta-analyses or systematic reviews (44)(45)(46)(47)(48).…”
Section: Summary Statementmentioning
confidence: 79%
“…Studies evaluating the role of ultrasound-assisted ET have had mixed results, and although meta-analysis of prospective trials has suggested an improvement in outcome, limitations in the study designs may overstate the effect of ultrasonography (34,35). Other ET techniques may eliminate the advantages provided by ultrasonography, limiting its benefits to specific clinical scenarios (36).…”
Section: Resultsmentioning
confidence: 99%